Validation of a child emotional learning activity kit using the fuzzy Delphi technique - Uzzairah Nabila Ahmad Tazli; Zaharah Osman; Nadia Shahira Amiruddin; Mazlina Che’ Mustafa (Institute of Advanced Engineering and Science, 2026)
Early childhood is a critical period for socio-emotional development, yet parents often lack structured tools to reinforce these skills at home. The study aims to obtain the experts’ unanimous agreement on the contents and components of an emotional learning activity kit for children. This study used the fuzzy Delphi method (FDM) to gather feedback from 13 experts in early childhood education. The survey contained 27 items, which used the seven-point Likert scale. FDM data was analyzed using triangular fuzzy numbers (TFN). The results of the study demonstrated consensus of the construct is at a high level. The overall expert consensus agreement exceeds 75%, the overall value of the threshold (d) is 0.2, and the α-cut exceeds 0.5. The value of the learning contents showed that the expert agreement of this kit is highly acceptable. Findings also showed learning material in this kit has a high agreement value, and it can be used to empower teachers and parents to cultivate their children’s emotional learning, bridging the gap between curriculum and home-based learning. Future research should consider expanding the application of this emotional learning activity to children in preschool.